BUSINESS PROCESS CONTEXT ANALYSIS BASED ON "EVENT LOG" - Airlangga Adi Hermawan (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2014)
Nowadays, information systems in organizations logged many kinds of event logs. These logs can be analyzed with process mining. The goal of process mining is to extract information from event logs and use it as an insights into the business process of the organizations. Unfortunately, most process mining techniques only consider process instance in isolatkategorialnfluence the analysis of the organizations. In this paper, we developed an approach to get insights in to context-related information based on event logs, such that useful insights can be easily obtained. Our approach has been evaluated through two case studies. The evaluation outcome confirms that most of the context-related information from event logs can be analyzed.Keywords : Big Data, Business Process, Process Mining